Solonnikov parabolic systems with quasihomogeneous structure - Ivasyshen, S. D.; Ivasyuk, H. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider a new class of systems of equations that combine the structures of Solonnikov and Éidel’man parabolic systems. We prove a theorem on the reduction of a general initial-value problem to a problem with zero initial data and a theorem on the correct solvability of an initial-value problem in a model case.